Differences in Imbibition Efficiency Between Bedding and Tectonic Fractures in the Lucaogou Formation in the Jimusar Sag: Evidence From Simulation Experiments - Liang, Chenggang; Liu, Aoran; Luo, Qun; Luo, Jiaguo; Li, Dong; Li, Peng (Frontiers in Earth Science, 2022)
In addition to tectonic fractures, the ubiquitous and important bedding fractures are often overlooked in the imbibition processes. Based on the identification of different fracture types in tight sandstone from the Middle Permian Lucaogou Formation in the Jimusar Sag, NW China, spontaneous imbibition of water experiments was carried out, aiming to investigate the effect of tectonic and bedding fractures on hydrocarbon recovery efficiency in tight reservoir rocks. The results show that the difference in connectivity between the vertical (tectonic fractures) and horizontal (bedding fractures) directions of pores and pore throats is the main reason for the distinction in microscale permeability and hence fluid imbibition. The difference in the time required for imbibition between bedding and tectonic fractures is subtle, but the former is slightly lower than the latter in terms of imbibition depth and efficiency. Higher temperature can shorten the reaction time of imbibition. On the basis that the tectonic fractures are opened,opening the same scale of bedding can increase the imbibition effectiveness by 8.7% at reservoir conditions (27MPa, 80˚C), and the closer to the fracture, the higher the imbibition efficiency in the matrix. The samples with higher porosity and permeability per unit volume have high imbibition oil recovery. However, the imbibition efficiency of the samples with lower porosity and permeability is higher, i.e., the final imbibition efficiency is inversely proportional to porosity and permeability.